(untitled) (Journal of Applied Oral Science, 2011)
OBJECTIVE: Hydroxyl (OH-) and calcium (Ca++) ion release was evaluated in six materials: G1) Sealer 26, G2) White mineral trioxide aggregate (MTA), G3) Epiphany, G4) Epiphany + 10% calcium hydroxide (CH), G5) Epiphany + 20% CH, and G6) zinc oxide and eugenol. MATERIAL AND METHODS: Specimens were placed in polyethylene tubes and immersed in distilled water. After 3, 6, 12, 24, and 48 h, 7, 14, and 28 days, the water was assessed for pH with a pH meter and for Ca++ release by atomic absorption spectrophotometry. RESULTS: G1, G2, G4, and G5 had the highest pH until 14 days (p